PENGARUH MOTIVASI DAN KOMPENSASI TERHADAP KEPUASAN KERJA DOSEN DI SEKOLAH TINGGI ILMU KOMPUTER CIPTA KARYA INFORMATIKA - Veri Arinal; Agus Tanti Rahayu (CKI ON SPOT, 2017)
The aim of this research is to know the influence of motivation and compensation to job satisfaction lecturer at Sekolah Tinggi Ilmu Komputer Cipta Karya Informatika (STIKOM CKI). The method of this research is quntitative method. There are two kinds variable involved, independent and dependent. Motivation and compensation as the independent variable and job satisfaction lecturer as the dependent variable. Data were collected through a interview and questionnares. The population of the research all over the number of lecturer in Sekolah Tinggi Ilmu Komputer Cipta Karya Informatika (STIKOM CKI) is a number of 31 people. Sampling method that used is saturated sampling. The data analysis using test validity, the reliability test, the classic assumption test, and to test the hypothesis using multiple linear regresions analysis, testers hypothesis statistics consisting of parcial test (t test), simultant test (f test), the coefficient determinasi and correlation. The result of this research shows that motivation and compensation have positive and significant effect in job satisfaction faculty lecturer at Sekolah Tinggi Ilmu Komputer Cipta Karya Informatika (STIKOM CKI). Based on that result, it is suggested to give more attention to job satisfaction lecturers through motivation and compensation as a whole. Keyword: compensation, motivation and job satisfaction